Aspects Of Travel Literature In The Desert Domain Alwargilani Trip As A Model (Journal of Human Sciences, 2021)
This research paper deals with aspects of travel writing in desert area throughAlwarjalany pilgrimage a cross Fezzan region, which took place during the second half of the  6th century migration/ the 12th century. The paper also seeks to study a new type of travel writing which differs from typical travel texts in terms of its form and style of writing. Additionally, the blogger of this travel had built a travel text in which all the elements of travel writing exist. Since Alwarjalany trip is a model of this type, the current study has traced its route and the way it had been recorded, by highlighting some of its writing features as well as the challenges and the dangers which encountered pilgrims who had joined the trip.